ANALYSIS OF HOTEL BRANDING STRATEGY IN ENHANCING CUSTOMER LOYALTY - Nilazarni; Luthfiar Ramiady (GREET, 2026)
The increasing competition in the hospitality industry has encouraged hotels to develop strong branding strategies to attract and retain customers. This study aims to examine the effect of hotel branding strategy on customer loyalty, with customer satisfaction as a mediating variable. Drawing upon branding theory and consumer behavior theory, this research proposes that a strong brand identity and image serve as important factors influencing customers’ perceptions and long-term relationships with the hotel. A quantitative approach was employed using survey data collected from hotel guests who have experienced hotel services. The data were analyzed using SPSS to test both direct and indirect relationships among variables. The findings indicate that hotel branding strategy has a significant effect on customer loyalty, both directly and indirectly through customer satisfaction. Customer satisfaction is found to partially mediate the relationship, suggesting that customers are more likely to become loyal when branding strategies enhance their overall experience and satisfaction. This study contributes to the hospitality marketing literature by providing empirical evidence on the role of branding in shaping customer loyalty and offers managerial implications for hotel management in developing effective branding strategies to sustain competitive advantage.